Model Pertumbuhan Harga Cabai Keriting (Capsicum annum L) (Suatu Kasus pada Sentra Produksi dan Pasar Induk Cabai Merah Keriting ) - Dety Sukmawati (Paspalum: Jurnal Ilmiah Pertanian, 2018)
Agricultural commodity trading generally involves various groups of traders such as village traders, district traders, district traders, inter-provincial traders and retailers in consumer areas. This market system can occur due to lack of competition among village traders and limited number of traders. Even if the number of traders that involved quite a lot but in its activities the traders are often controlled by one or several traders. This research includes quantitative research by using time series data of price of curlychili in Cikajang production center, Caringin Wholesale Market, Gedebage Wholesale Market and Kramat Jati Wholesale Market in 2014 and data of price development and production of red curry pepper in 2009-2014, data analysis used is Eviews 8 Program. The price growth model at the wholesale for the lowest initial price was PIC (y = 10592 + 154.48x), highest PIG (y = 10759 + 180.03x). In this case the price at the highest PIG, indicating the channel price of the PIC and PIKJ (y = 11245 + 169.21x). The price growth model stated that price developments in 4 places, at fluctuating prices can be illustrated by the growth model, although a stable price is something to be expected with a variety of factors that are in fact difficult to achieve. The fixed price growth model remains the lowest price in production centers or farmers.